Who Gets Vaccinated? Cognitive and Non-cognitive Predictors of Individual Behavior in Pandemics - Mark A. Andor; Thomas K. Bauer; Jana Eßer; Christoph M. Schmidt; Lukas Tomberg (Institute of Labor Economics (IZA), 2023)
This study investigates the different cognitive and non-cognitive characteristics associated with individuals' willingness to get vaccinated against Covid-19 and their actual vaccination status. Our empirical analysis is based on data obtained from three survey waves of about 2,000 individuals living in the German state of North Rhine-Westphalia. We find that individuals with a high level of trait reactance display a significantly lower willingness to get vaccinated. They also tend to get inoculated later or never. Moreover, neuroticism, locus of control, and risk literacy appear to be associated with the willingness to get vaccinated, but these results are less pronounced and less robust. Our results indicate that vaccination campaigns and policies could be improved by specifically addressing those with a high level of trait reactance.
Keywords: D91; H0; I12; I18; 330; COVID-19; vaccination; psychological traits; risk literacy; health literacy